1962
DOI: 10.3327/jaesj.4.117
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Inorganic Ions with Tri-n-octyl Phosphine Oxide

Abstract: The extraction behavior of about sixty inorganic ions was studied in the respective systems of tri-n-octyl phosphine oxide** -HCl and -HNO3 for a contribution to the radio chemical separation techniques.TOPO was dissolved in toluene and used as its 5% (w/v) solutions. The dis tribution ratios for each elements were det ermined in the same way as previous works. The acid dependence curves were obtained

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1964
1964
1981
1981

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The Rf values for the movement of the lanthanide nitra.tes on HDPMimpregnated paper, Figures 2 and 4 In agreement with partition data (16) a definite singularity is seen a t gadolinium, Figures 2 and 3, and the slightly higher R f for this element is expected by analogy with the sl ghtly lower than average partition coefficient into TBP. No singularity existed for cerium in the T B P extraction data and the unusually low R, values obtained are Table V.…”
Section: Movement Of Metal Perchlorates As a Function Of Acid Concentsupporting
confidence: 73%
See 3 more Smart Citations
“…The Rf values for the movement of the lanthanide nitra.tes on HDPMimpregnated paper, Figures 2 and 4 In agreement with partition data (16) a definite singularity is seen a t gadolinium, Figures 2 and 3, and the slightly higher R f for this element is expected by analogy with the sl ghtly lower than average partition coefficient into TBP. No singularity existed for cerium in the T B P extraction data and the unusually low R, values obtained are Table V.…”
Section: Movement Of Metal Perchlorates As a Function Of Acid Concentsupporting
confidence: 73%
“…This was predicted for the extraction of uranium(V1) with T B P a t 4 M nitric acid. It should be noted, however, that Hesford, Jackson, and McKay (16) found that the partition coefficients for the extraction of the lanthanides into 100% T B P increased monotonically with nitric acid concentration. Also the column data of Fidelis and Siekierski (7, 8) indicate that the lanthanide nitrates are held progressively tighter as the nitric acid concentration is increased.…”
Section: Movement Of Metal Nitrates Asmentioning
confidence: 93%
See 2 more Smart Citations
“…Survey studies on the extractability of a large number of metal nitrates from nitric acid solution in the range from 1-15 M into tributylphosphate, (77) trioctylphosphine oxide (340,341) and some diphos-phates^7 , 341) have become available during the period under review. Survey studies on the extractability of a large number of metal nitrates from nitric acid solution in the range from 1-15 M into tributylphosphate, (77) trioctylphosphine oxide (340,341) and some diphos-phates^7 , 341) have become available during the period under review.…”
Section: Metal Extractionmentioning
confidence: 99%